JUDICIAL INDEPENDENCE IN GERMANY (Law and world, 2015)
The presentation will briefly outline the way by which Germany has attempted to safeguard judicial independence. Article 97 of Germany’s Basic Law, or Constitution, specifically refers to and guarantees judges’ independence without, however, granting an individual right. Rather, judicial independence is seen as a basic constitutional principle, which ensures the realisation of the rule of law.